2019
DOI: 10.1073/pnas.1905722116
|View full text |Cite
|
Sign up to set email alerts
|

Cell division rates decrease with age, providing a potential explanation for the age-dependent deceleration in cancer incidence

Abstract: A new evaluation of previously published data suggested to us that the accumulation of mutations might slow, rather than increase, as individuals age. To explain this unexpected finding, we hypothesized that normal stem cell division rates might decrease as we age. To test this hypothesis, we evaluated cell division rates in the epithelium of human colonic, duodenal, esophageal, and posterior ethmoid sinonasal tissues. In all 4 tissues, there was a significant decrease in cell division rates with age. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 39 publications
7
64
0
Order By: Relevance
“…of cancer cells. Recent in vivo work shows the cell division rate in stem cells declines with age(Tomasetti et al 2019), and we validate these findings mathematically, for the first time in cancer cells, showing the rate of proliferative decline is not uniform across all melanoma subtypes. Our framework can be used to test if the age-driven decline in cell division varies depending on the tissue of origin, and whether the lineage-specific cell division decline mirrors a decrease in cancer incidence observed in the very elderly population.…”
supporting
confidence: 71%
“…of cancer cells. Recent in vivo work shows the cell division rate in stem cells declines with age(Tomasetti et al 2019), and we validate these findings mathematically, for the first time in cancer cells, showing the rate of proliferative decline is not uniform across all melanoma subtypes. Our framework can be used to test if the age-driven decline in cell division varies depending on the tissue of origin, and whether the lineage-specific cell division decline mirrors a decrease in cancer incidence observed in the very elderly population.…”
supporting
confidence: 71%
“…In our previous research, we showed the fundamental role played by the number of cells, and the number of cell divisions, in determining cancer risk 15,[23][24][25] . A natural question is then to ask whether obesity has an effect on the size of our organs, and therefore on their total numbers of cells.…”
mentioning
confidence: 99%
“…And harmful inherited mutations appear to explain only a very small percentage (<5%) of obesity 7 . This is somewhat surprising since cancer is by and large the result of deleterious genetic and epigenetic changes as described by the somatic mutation theory of cancer [8][9][10] and successively solidified by genome-wide analyses [11][12][13][14][15][16] . How can obesity increase the risk of cancer if it does not increase a cell's mutational load?…”
mentioning
confidence: 99%
“…As the body ages, the innate immune system gradually declines, a phenomenon now termed immunosenescence [145], resulting in decreased effector immune cell function; and healthy tissue renewal rate decreases dramatically [146]. As a result, the aged tissue microenvironment accumulates senescent cells, such as SASP-associated fibroblasts, and gains the infiltration of immune infiltrates such as immunosuppressive myeloid-derived suppressor cells (MDSCs) and T regulatory cells.…”
Section: The Ageing Immune System and Immunosenescencementioning
confidence: 99%